Eksplorasi Kebutuhan Pengembangan Modul Fisika Berbasis Etno-STEM dan Diferensiasi untuk Meningkatkan Berpikir Kritis Siswa SMA dalam Konteks Pemanasan Global di Sumatera Selatan - Hamdi Akhsan; Ismet; Kistiono (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify the empirical needs for developing an Ethno-STEM-based and differentiated physics module to improve critical thinking skills among high school students in South Sumatra, within the context of global warming. A mixed-methods exploratory sequential design was employed, with qualitative data from open-ended questions informing the development of a quantitative Likert-scale questionnaire administered to 81 physics teachers and 1,118 Grade 10 students across five vulnerable districts. Results show that while 100% of teachers express interest in Ethno-STEM, only 24.7% have implemented it, primarily due to the lack of ready-to-use modules (32.4%) and curriculum time constraints (27.0%). Students exhibit diverse learning preferences, with 74.6% favoring hands-on experiments. Furthermore, 83.5% demonstrate analytical skills by identifying causes of environmental problems, but only 61% can compare solutions effectively. These findings reveal a significant gap between awareness and practice, underscoring the urgent need for contextual, culturally responsive, and differentiated learning materials. The study provides a strong empirical foundation for designing a project-based physics module aligned with the Merdeka Curriculum, integrating local wisdom, STEM principles, and learning style differentiation to enhance critical thinking.